Factors Affecting Utilization of Maternal Health Care Services in Kombolcha District, Eastern Hararghe Zone, Oromia Regional State, Eastern Ethiopia. (29th October 2014) - Zelalem Ayele, Desalew; Belayihun, Bekele; Teji, Kedir; Admassu Ayana, Desalegn
Abstract : Introduction. World health organization estimates that more than half a million women lose their lives in the process of reproduction worldwide every year and most of these mortalities are avoidable if mothers have access to maternal health care services. Objectives. This study was conducted with objectives of determining the prevalence of utilization of maternal health care services and identifying factors affecting it. Methodology. A community based cross-sectional survey was conducted in six kebeles of Kombolcha district. A total of 495 women of reproductive age participated in the study and their selection was made using simple random sampling technique and data was collected using an interviewer-administered structured questionnaire. The data was analyzed using SPSS version 16. Results. A total of 495 women were included in this study and from these women about 86.1% had at least one ANC visit during their last pregnancy. About 61.7% of mothers had less than four visits which is less than the recommended and 46.2% started it in the second trimester. Only 25.3% of respondents gave birth in health institutions and rural women were less likely to use institutional delivery 20.9% compared to urban women 35.9%. Recommendations. More efforts should be given to educate society in general and mothers in particular, to strengthen community participation and to increase the accessibility of maternal health care services. Moreover, providing accurate information about the services provided in the health institutions is required from the concerned governmental and nongovernmental organizations.